Use of paracetamol in ischaemic stroke patients: evidence from VISTA. (15th February 2013) - Frank, B.; Fulton, R. L.; Weimar, C.; Lees, K. R.; Sanders, R. D.; ,
<x xml:space="preserve">Abstract</x> Objectives Paracetamol is frequently prescribed for pain and fever control in acute stroke patients, but its effect on stroke outcome is unclear. The aim was to investigate the safety and benefit of paracetamol administration in the acute phase of ischaemic stroke. Methods We analysed the impact of paracetamol exposure on functional outcome at 90 days among ischaemic stroke patients registered in a clinical trials archive. We used an adjusted Cochran–Mantel–Haenszel test to test for significance (P) followed by proportional odds logistic regression analysis to estimate the odds ratios (OR) for more favourable modified Rankin Scale score. Results Data were available for 6015 patients, of whom 2435 had received paracetamol. No association of paracetamol‐use with overall stroke outcome could be detected among those patients who experienced pain and/or fever (OR 1.03, 95% CI 0.86–1.20, P = 0.931). In patients without recorded pain and/or fever events and a baseline temperature below 37°C, in whom paracetamol was started within 3 days of stroke, paracetamol was associated with worse outcome (OR 0.58, 95% CI 0.47–0.72, P = <0.001). Conclusion This retrospective analysis is discouraging for prophylactic use of paracetamol in acute stroke patients, but underlines the need for a sufficiently powered randomized controlled trial.